Pricing determinants and decisions in financial services - Estelami, Hooman (Henry Stewart Talks, 2008)
Unique aspects of pricing financial services, Common pricing methods: cost based pricing, parity pricing, value based pricing, regulation based pricing, Category specific pricing practices, Common practices, Pricing of credit products, Pricing of savings products, Pricing brokerage services, Pricing insurance products, Estimating the demand function, Strategic considerations in pricing financial services